Analisis Kebijakan Desentralisasi Pendidikan pada Tingkat Sekolah Dasar: Kajian Implementasi dan Implikasi terhadap Mutu Pendidikan - Siti Ni'matul Fitriyah; Syamsul Hadi; Radeni Sukma Indra Dewi (Jurnal Ilmiah Global Education, 2026)
Decentralization of education transfers authority from the central government to local governments and schools to improve the relevance and effectiveness of educational services. This study aims to analyze the implementation of basic education decentralization policies, and examine their implications for the quality of education. The analysis was conducted on national regulations and a number of local regulations from Surabaya, Yogyakarta, and Palangka Raya. The results of the study show that decentralization is realized through three main pillars: decentralization of authority, decentralization of curriculum, and decentralization of budget. Regional implementation shows a variety of strategies, ranging from the establishment of mandatory local content, the provision of school-based curricular autonomy, to the development of culture-based local curricula. The implications include increased learning relevance, room for innovation for teachers, and strengthening of cultural identity, although there are still challenges in terms of regional capacity, budget accountability, and quality gaps between regions. These findings confirm that decentralization has the potential to strengthen the quality of basic education if accompanied by capacity building and effective monitoring mechanisms.